Investigation of the relationship between the humour styles and trait anxiety levels of students attending schools of physical education and sports - KÜÇÜK, VEYSEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
This study aimed to investigate the relationship between School of Physical Education and Sports students' humour styles and trait anxiety levels. This study sample was composed of 607 randomly selected students attending five different Schools of Physical Education and Sports in Turkey during the spring term of the 2014-2015 academic year. As a result, significant and reverse relationships were found with positive humour styles Self-enhancing humour' and Affiliative humour' and positive and meaningful relationships were detected with negative humour styles Aggressive humour' and Self-defeating humour'.
Keywords: UNIVERSITY-STUDENTS; QUESTIONNAIRE; PERSONALITY; EXERCISE; HEALTH